2020
DOI: 10.1097/yic.0000000000000304
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, double-blind study comparing the efficacy and safety of trazodone once-a-day and venlafaxine extended-release for the treatment of patients with major depressive disorder

Abstract: This double-blind, randomized study evaluated the efficacy and safety of trazodone OAD (once-a-day) in comparison with venlafaxine XR (extended-release) in 324 patients (166 trazodone and 158 venlafaxine) with major depressive disorder (MDD). The primary efficacy endpoint was the mean change from baseline in the 17-item Hamilton Depression Rating Scale (HAM-D) at week 8. Both treatments were effective in reducing the HAM-D-17 total score at week 8 vs. baseline (intent-to-treat: trazodone –12.9, venlafaxine –14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…44,45 Analysis of variance (ANOVA) was used in cases where the statistical assumptions of ANCOVA were not met. 44 Two-sided 95% confidence intervals (CIs) were calculated for the differences in mean score change from baseline for trazodone OAD vs placebo, as well as trazodone OAD vs venlafaxine XR, for the same HAM-D17 outcomes analyzed by ANCOVA or ANOVA. 44 For trazodone OAD vs venlafaxine XR, the noninferiority was accepted if the upper limit of the 95% CIs for the difference between treatments did not surpass the threshold of 3, which represented the maximum difference associated with no clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…44,45 Analysis of variance (ANOVA) was used in cases where the statistical assumptions of ANCOVA were not met. 44 Two-sided 95% confidence intervals (CIs) were calculated for the differences in mean score change from baseline for trazodone OAD vs placebo, as well as trazodone OAD vs venlafaxine XR, for the same HAM-D17 outcomes analyzed by ANCOVA or ANOVA. 44 For trazodone OAD vs venlafaxine XR, the noninferiority was accepted if the upper limit of the 95% CIs for the difference between treatments did not surpass the threshold of 3, which represented the maximum difference associated with no clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…48,49 Therefore, we also reviewed the efficacy of trazodone OAD in improving In the placebo-controlled study, conducted by Sheehan et al, 45 trazodone OAD showed a trend for early improvement at Day 7 in the HAM-D anxiety/somatization factor compared to placebo; however, this difference was statistically significant only at Day 21 for both the ITT [95% CI, À1.0; À0.1] and the PP [95% CI, À1.3; À0.2] populations (P < .05) (Figure 2A and Supplementary Figure S3A). In the active-comparator study by Fagiolini et al, 44 both trazodone OAD and venlafaxine showed similar improvements in the anxiety/somatization factor at Day 7, and the difference between the groups was statistically significant in the favor of venlafaxine XR at Days 35 [95% CI, 0.1; 1.0] and 56 [95% CI, 0.3; 1.3] for the ITT population and only at Day 56 [95% CI, 0.0; 1.0] for the PP population (P < .05) (Figure 2B and Supplementary Figure S3B).…”
Section: Early Improvement Of Depressive Symptoms With Trazodone Oad Formulationmentioning
confidence: 99%
“…A phase‐III study of aripiprazole was terminated due to the risk of late neuroleptic malignant syndrome in treated patients (NCT00276978) [124] and no new safety signals were observed [125] . Trazodone, a serotonin modulator, [126] completed the phase‐II and III trial in which the efficiency of its prolonged‐release tablets was determined in depressive patients (NCT01524497) [127–128] . A phase‐III study of another drug olanzapine was also terminated (NCT00273624) as augmentation therapy in treatment‐resistance depression.…”
Section: Piperazine Derivatives In Clinical Trials For Depressionmentioning
confidence: 99%
“…The availability of different formulations (Table III) ensures the efficacy of trazodone in a wide range of 22 . The relatively short elimination half-life (6h) reduces the risk of morning drowsiness 30 . The prolonged-release (P.R.)…”
Section: Formulationsmentioning
confidence: 99%
“…The extended-release (COAD) formulation provides an even more gradual and continuous absorption of the drug into the bloodstream. It allows a simplified once-a-day prescription schedule, thus enhancing adherence, improving tolerability, and avoiding see-sawing blood concentration patterns 30 .…”
Section: Formulationsmentioning
confidence: 99%